Infant feeding in the second 6 months of life related to iron status: an observational study. Issue 10 (30th May 2007) - Hopkins, David; Emmett, Pauline; Steer, Colin; Rogers, Imogen; Noble, Sian; Emond, Alan
Abstract : Objective: To investigate the relationship between iron status in infancy and type of milk and weaning solids consumed. Design: An observational cohort study. Setting: 928 term infants from the Avon Longitudinal Study of Parents and Children in 1993–94. Methods: Haemoglobin and ferritin concentrations at 8 and 12 months were assessed in relation to type and quantity of milk intake at 8 months. Results: By WHO criteria, 22.7% of the infants were anaemic at 8 months and 18.1% at 12 months. More breast- than formula-fed infants were anaemic at 8 and 12 months. Cows' milk as the main drink was associated with increased anaemia at 12 months and low ferritin at 8 and 12 months. No association was found between any nutrients and haemoglobin concentrations. Protein and non-haem iron intakes were positively associated with ferritin concentrations and calcium intake negatively. This effect was more marked in infants being fed cows' milk. More than 25% of infants in the breast milk and cows' milk groups and 41% of infants having >6 breast feeds per day had iron intakes below the lower reference nutrient intake. Feeding cows' milk or formula above 600 ml or >6 breast feeds per day was associated with lower intakes of solids. Conclusions: Both breast and cows' milk feeding were associated with higher levels of anaemia. Satisfactory iron intake from solids in later infancy is more likely if formula intake is <600 ml per day and breast feeds are limited to <6 feeds per day. Cows' milk should be strongly discouraged as a main drink before 12 months.